Mahar Berupa Rumah Dan Pertapakannya - Abdullah Zaman; Ahmatnijar Ahmatnijar; Dermina Dalimunte (Jurnal El-Thawalib, 2021)
This thesis is entitled Mahar in the form of a house and its hermitage (Case Study 54/Pdt.G/2016/PA.Psp The purpose of this research is how the decision of the Padangsidimpuan Religious Court against the dowry suit in the form of a house and its hermitage, what is the judge's consideration in determining the decision on the dowry suit in the form of a house and hermitage by the plaintiff to the defendant.  The problem in this study is that at the time of mentioning and handing over the dowry the groom gives a dowry/dowry in the form of his house and hermitage, but at the time of ijab qabul, the marriage registrar (P3N) does not ask whether the house and the hermitage really belong to the groom and do not ask for a certificate issued by the groom. legally shows that the house and hermitage really belong to the groom. After getting married they lived together in a house which became the dowry of the marriage.  The marriage lasted for approximately one year, there were quarrels and quarrels that led to divorce so that the wife sued her husband to the Padangsidimpuan religious court demanding a dowry in the form of a house and hermitage which was used as a dowry at the time of consent and qabul. This  type of research is a qualitative research. The subject of this research is the judge of the Padangsidimpuan Religious Court. The data sources of this research are primary data and secondary data. Data collection techniques are interviews and documentation. The data processing technique is descriptive analysis, namely presenting data or research results clearly and in detail. The data analysis technique of this research is to systematically search and compile the data obtained from interviews and documentation in the form of the judge's decision, by organizing the data into categories, describing it into units, synthesizing, compiling into patterns, choosing which ones are important. and what will be studied and draw conclusions.  The results of this study are that the judge in resolving the dowry case in the form of the house and its hermitage, in the legal regulations in Indonesia, namely in articles 30-33 of the KHI in considering the decision of the dowry case in the form of a house and hermitage in the Padangsidimpuan religious court case study no 54/Pdt/ .G/2016/PA.Psp.